Hepatic microsomal UDP‐glucuronosyltransferase (UGT) activities in the microminipig. (21st May 2014) - Higashi, Eriko; Ando, Akihiro; Iwano, Shunsuke; Murayama, Norie; Yamazaki, Hiroshi; Miyamoto, Yohei
ABSTRACT The microminipig, a small minipig, was bred as a novel experimental animal for nonclinical pharmacology/toxicology studies by Fuji Micra Inc. (Shizuoka, Japan). Species differences in drug metabolism between humans and the microminipig need to be elucidated in more detail in order to discuss the results of nonclinical studies. Glucuronidation catalysed by UDP‐glucuronosyltransferase (UGT) is an important pathway in the metabolism of a wide variety of compounds. The aim of the present study was to identify the characteristics of hepatic UGT activity in the microminipig and compare them with those in humans and other experimental animals. This study examined in vitro UGT activities using liver microsomes from microminipigs (8 months old and 1 day old), humans, mice, rats, dogs, monkeys and minipigs. The glucuronides of estradiol, imipramine, serotonin, propofol, 3′‐azido‐3′‐deoxythymidine (AZT) and morphine, selective substrates of human UGT1A1, 1A4, 1A6, 1A9 and 2B7 (AZT and morphine), respectively, were measured using LC‐MS/MS. Estradiol‐3‐glucuronidation activity was higher in the microminipig than in humans and the other animals. High levels of estradiol‐3‐glucuronidation were observed in the microsomes of 1‐day‐old microminipigs. Imipramine‐N‐glucuronidation, a distinctive conjugation by human UGT1A4, was catalysed by microminipig liver microsomes, but not by dog liver microsomes. Although AZT‐glucuronidation activity was low in the microminipig compared with humans, morphine‐3‐glucuronidation activity in the microminipig was higher than that in humans. The UGT activities in the microminipig were similar to those in the minipig. The results of the present study have provided useful information for selecting an appropriate animal model for nonclinical studies. Copyright © 2014 John Wiley & Sons, Ltd.